Disentangling public opinion on European integration: On the multidimensionality of integration attitudes - Lukas Lauener (European Union Politics, 2026)
This study explores citizens’ attitudes towards European integration, moving beyond a simplistic ‘yes’ or ‘no’ perspective. Focusing on the EU–Swiss relationship, it examines a variety of integration questions using 2019 Swiss Election Study data. Latent profile analysis identifies five citizen groups that share similarities in support and opposition patterns regarding the studied questions: ‘pure sovereignists’, ‘neutrals’, ‘pure integrationists’, ‘cultural sovereignists’ and ‘economic integrationists’. The latter two groups are both comparatively more favourable of economic than cultural European integration, substantiating the claim that integration attitudes are multidimensional. Investigating the predictors of adherence to these two groups, the study finds education, income and party vote intentions to have a differentiated effect. Relevant group comparisons show that education and radical right vote intentions differentiate positions along the cultural, but not the economic, European integration dimension, whereas income, radical left and liberal vote intentions differentiate positions along the economic, but not the cultural, dimension.